2015
DOI: 10.1001/jamaophthalmol.2015.186
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Intravitreous Ranibizumab Injections for Diabetic Macular Edema and the Risk of Sustained Elevation of Intraocular Pressure or the Need for Ocular Hypotensive Treatment

Abstract: IMPORTANCE For the management of retinal disease, the use of intravitreous injections of anti-vascular endothelial growth factor has increased. Recent reports have suggested that this therapy may cause sustained elevation of intraocular pressure (IOP) and may potentially increase the risk of glaucoma for patients with retinal disease.OBJECTIVE To assess the risk of sustained IOP elevation or the need for IOP-lowering treatments for eyes with diabetic macular edema following repeated intravitreous injections o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 22 publications
(50 reference statements)
1
52
0
2
Order By: Relevance
“…There were five RCTs1920212223 and 17 non-RCT studies1415161724252627282930313233343536. The latter group included 11 retrospective case series1417242526272829303132, two prospective studies3334, and four post hoc analyses15163536. Follow-up in the included articles ranged from 2.2627 to 6031 months.…”
Section: Resultsmentioning
confidence: 99%
“…There were five RCTs1920212223 and 17 non-RCT studies1415161724252627282930313233343536. The latter group included 11 retrospective case series1417242526272829303132, two prospective studies3334, and four post hoc analyses15163536. Follow-up in the included articles ranged from 2.2627 to 6031 months.…”
Section: Resultsmentioning
confidence: 99%
“…Anti-vascular endothelial growth factor (VEGF) agents have also been associated with elevated IOP, in as many as 12% of cases. Several mechanisms have been suggested for this adverse effect, including toxic changes, transient inflammation with production of cytokines that promote IOP elevation, and mechanical blockage of the trabecular meshwork [44-48]. …”
Section: Considerations Before Injectionmentioning
confidence: 99%
“…A mean of 7 ± 4 injections were given to the 22 eyes that met the primary outcome measure, compared to 15 ± 8 in the remaining eyes. Therefore, the number of injections was not associated with an increased risk of sustained IOP elevation [12] . No patients required laser or incisional surgery to achieve IOP control.…”
Section: Risk Of Iop Elevation In Patients Receiving Ranibizumabmentioning
confidence: 89%
“…These patients revealed an 8.3 versus 15.0% cumulative probability of the primary outcome measure at 3 years in the ranibizumab and sham cohorts, respectively, thereby resulting in a 6.6% difference (99% CI -8 to 21%; HR ranibizumab/sham = 1.9; 99% CI 0.7-5.1, p = 0.11) [12] . In summary, Protocol I data demonstrate no definitive link between ranibizumab and increased risk of glaucoma, but a trend of increased IOP was noted, and therefore the investigators suggested IOP monitoring during follow-up visits.…”
Section: Risk Of Iop Elevation In Patients Receiving Ranibizumabmentioning
confidence: 94%
See 1 more Smart Citation